Numerical Investigation on Primary Atomization Mechanism of Hollow Cone Swirling Sprays - Jia-Wei Ding; Guo-Xiu Li; Yu-Song Yu; Hong-Meng Li (International Journal of Rotating Machinery)
The atomization process of swirling sprays in gas turbine engines has been investigated using a LES-VOF model. With fine grid resolution, the ligament and droplet formation processes are captured in detail. The spray structure of fully developed sprays and the flow field are observed firstly. A central recirculation zone is generated inside the hollow cone section due to the entrainment of air by the liquid sheet and strong turbulent structures promote the breakup of ligaments. At the exit of injector nozzle, surface instability occurs due to disturbance factors. Axial and transverse mode instabilities produce a net-like structure ligament zone. Finally, the generation mechanism of the droplet is analyzed. It is found that the breakup mechanism of ligaments is located at the Raleigh capillary region. Axial symmetry oscillation occurs due to the surface tension force and the capillary waves pinch off from the neck of the ligaments. Secondary breakup and coalescence occur at the “droplet zone,” resulting in a wider distribution curve at the downstream area.